Prospects for the expansion of language policies in the Bangsamoro education code - Louis Dreisbach, Jeconiah; Mendoza-Dreisbach, Sharon (Penerbit Universiti Kebangsaan Malaysia, 2023)
In 2019, the Bangsamoro Parliament passed a legislation concerning the establishment of an education system that specifically caters to the learners of the Bangsamoro Autonomous Region of Muslim Mindanao. It defines where the Arabic language will be used for in ‘Madaris’ (Islamic educational institutions), who are qualified Arabic teachers, the general curriculum structure of the Bangsamoro public school system, and a mention of the nonMuslim Indigenous Peoples’ language and culture in their education system. Considering the Islamic orientation of the Bangsamoro education system within the overall Philippine education framework, the Bangsamoro Education Code primarily focuses on the Arabic, English, and Filipino languages as the primary linguistic requirements for educators, administrators, and mediums of instruction in the schools. The mother tongue of the learners is also an option as a medium of instruction in their educational linguistic landscape. However, existing studies found that Bangsamoro students struggle with the Arabic and English languages. Moreover, non-Muslim Indigenous Peoples are severely marginalized as there are no existing studies that could include them in the discourses. Grounded in applied linguistic and policy studies, this review article mentioned legislation in triangulation with existing linguistic studies on the region and developed prospective ways improve and expand the Bangsamoro Education Code.